2019
DOI: 10.1111/pce.13615
|View full text |Cite
|
Sign up to set email alerts
|

Root cortical anatomy is associated with differential pathogenic and symbiotic fungal colonization in maize

Abstract: Root anatomical phenotypes vary among maize (Zea mays) cultivars and may have adaptive value by modifying the metabolic cost of soil exploration. However, the microbial trade‐offs of these phenotypes are unknown. We hypothesized that nodal roots of maize with contrasting cortical anatomy have different patterns of mutualistic and pathogenic fungal colonization. Arbuscular mycorrhizal colonization in the field and mesocosms, root rots in the field, and Fusarium verticillioides colonization in mesocosms were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 90 publications
1
35
0
Order By: Relevance
“…Improve-ment of aboveground traits during maize evolution had unintended belowground effects that likely impacted rhizosphere interactions. For example, both domestication and agricultural intensification affected maize root system architecture, which can affect rhizobiome composi-tion (Corneo et al, 2016), and anatomy, which can affect pathogenic and symbiotic fungal colonization (Galindo-Castan~eda et al, 2019). Domestication led to longer nodal roots, more seminal roots, more aerenchyma, and greater genetic variation for anatomical and archi-tectural traits in landraces than teosinte (Burton et al, 2013), and reduced root branching despite equivalent root:shoot ratio (Gaudin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Improve-ment of aboveground traits during maize evolution had unintended belowground effects that likely impacted rhizosphere interactions. For example, both domestication and agricultural intensification affected maize root system architecture, which can affect rhizobiome composi-tion (Corneo et al, 2016), and anatomy, which can affect pathogenic and symbiotic fungal colonization (Galindo-Castan~eda et al, 2019). Domestication led to longer nodal roots, more seminal roots, more aerenchyma, and greater genetic variation for anatomical and archi-tectural traits in landraces than teosinte (Burton et al, 2013), and reduced root branching despite equivalent root:shoot ratio (Gaudin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Forrester et al (2020) noted a greater generalization in bacterial assemblages in autotetraploid individuals of Medicago sativa compared to diploids, suggesting that larger cells in polyploids could host a greater quantity of different bacterial symbionts, compared to smaller cells in diploids. In the case of fungi, Galindo-Castañeda et al (2019) reported a decrease in mycorrhizal colonization in Zea mays with a decrease in the living cortical area. In the case of Salicornia , our anatomical data showed no differences in cell size between the two cytotypes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The two species have a similar morphology and react highly plastic to changes in the environment, which makes morphology-based species identification challenging and time-consuming. In addition to that, there are no studies investigating whether the two cytotypes differ in root anatomical traits, which could directly influence fungal recruitment and community establishment, as observed for endophytic bacteria (Forrester et al 2020) and fungi (Galindo-Castañeda et al 2019). Because of the morphological similarities of the cytotypes, species identification is mostly conducted based on their differences in ploidy (Kadereit et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed below, root anatomical phenotypes could be important drivers of root and rhizosphere microbiomes, as well as other root-associated biota including nematodes and insects ( Lynch et al, 2021 ). For example, root cortical anatomy in maize is associated with differential effects on root colonization by Fusarium species and beneficial mycorrhizal fungi ( Galindo-Castañeda et al, 2019 ).…”
Section: Root Phenotypes As Breeding Targets To Develop Crops That Ar...mentioning
confidence: 99%